A Response to "An Interior of Inclusion or the Illusion of Inclusion". Issue 2 (June 2019) - Unknown
Letters offers a forum for sharing ideas, exchanging dialog, and stimulating conversations and debate on critical issues that impact the designed environment as presented in the Perspectives section of the Journal of Interior Design. Diversity has become a flashpoint on North America's political stage and beyond. It is not new but instead, and unfortunately, a part of our nation's fabric as noted by the struggles the interior design profession has had in its own attempts to more accurately reflect the diversity of the United States. In 2018, Jack Travis authored a Perspective published in the Journal of Interior Design. The following letters were received in response to assure that the conversation did not end there .